2005
DOI: 10.1007/s11284-005-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐up trophic cascades and material transfer in terrestrial food webs

Abstract: In contrast to top-down trophic cascades, few reviews have appeared of bottom-up trophic cascades. We review the recent development of research on bottom-up cascades in terrestrial food webs, focusing on tritrophic systems consisting of plants, herbivorous insects, and natural enemies, and attempt to integrate bottom-up cascade and material transfer among trophic levels. Bottom-up cascades are frequently reported in various tritrophic systems, and are important to determine community structure, population dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 87 publications
(95 reference statements)
3
75
1
2
Order By: Relevance
“…For example, Nakamura et al (2005) showed that increased foliage sprouting after a flood increased the abundance of leaf beetles and their natural enemies. It has also been shown that 'bottom-up' cascades can be triggered by allelochemical compounds of plants, but here the cascading effects on natural enemies are reported to be weak or absent (Kagata and Ohgushi 2006; but see Soler et al 2005;Ode 2006). This interruption of cascading effects by allelochemicals can be caused by herbivorous insects that are resistant to the plant's defensive toxins or by herbivores accumulating plant secondary compounds within their own body tissue and using them for their own defense against natural enemies (Barbosa et al 1991;Francis et al 2001).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, Nakamura et al (2005) showed that increased foliage sprouting after a flood increased the abundance of leaf beetles and their natural enemies. It has also been shown that 'bottom-up' cascades can be triggered by allelochemical compounds of plants, but here the cascading effects on natural enemies are reported to be weak or absent (Kagata and Ohgushi 2006; but see Soler et al 2005;Ode 2006). This interruption of cascading effects by allelochemicals can be caused by herbivorous insects that are resistant to the plant's defensive toxins or by herbivores accumulating plant secondary compounds within their own body tissue and using them for their own defense against natural enemies (Barbosa et al 1991;Francis et al 2001).…”
Section: Introductionmentioning
confidence: 76%
“…In contrast to 'top-down' cascades, most studies on 'bottom-up' cascades show directional responses that are the same for herbivores and their natural enemies, i.e. poor plant quality decreases herbivore population density as well as natural enemy performance and good plant quality enhances herbivore abundance as well as natural enemy performance (Hunter and Price 1992;Nakamura et al 2005;Kagata and Ohgushi 2006). For example, Nakamura et al (2005) showed that increased foliage sprouting after a flood increased the abundance of leaf beetles and their natural enemies.…”
Section: Introductionmentioning
confidence: 99%
“…First, resource availability and primary productivity may cascade up food webs (27), leading to a parallel increase in the abundance of intermediate predators and to an increase in the strength of top predator effects. In the exploitation ecosystems hypothesis, Oksanen et al (28) proposed that increasing primary productivity of a system should result in progressive lengthening of food chains and increasing abundance at higher trophic levels.…”
Section: Resultsmentioning
confidence: 99%
“…Interactions can also work in the other direction, referred to as bottom-up effects. For example, the chemical composition of plant tissue can affect the behaviour of natural enemies directly through chemical cues for finding prey or indirectly through the effects on herbivore populations (Kagata & Ohgushi 2006). While there is increased recognition of the importance of both top-down and bottom-up processes, a conceptual synthesis is lacking due to a paucity of experimental data, failure to utilize pre-existing datasets and a tendency to emphasize one process over the other (Walker & Jones 2001).…”
Section: Understanding Multitrophic Interactionsmentioning
confidence: 99%